SARS-CoV-2 and Streptococcus pneumoniae Coinfection in a Previously Healthy Child - Kimberly C. Vu; Gloria P. Heresi; Michael L. Chang (Case Reports in Pediatrics)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was first reported in December 2019 in Wuhan, China. This novel coronavirus has been responsible for a pandemic that continues to devastate nations worldwide. COVID-19, like other viruses, causes pneumonia. However, unlike other viral respiratory tract infections such as influenza, bacterial coinfection in COVID-19 patients has uncommonly been described in adult and pediatric patients. We report a case of Streptococcus pneumoniae and COVID-19 coinfection in a previously healthy 4-year-old child.